ANTIDIARRHEAL ACTIVITY OF ETHANOLIC EXTRACT OF MIMOSA PUDICA L. HERBS AGAINTS MALE MICE INDUCED BY OLEUM RICINI - Karunita Ika Astuti; Fitriyanti; Nur Huda (Borneo Journal of Pharmascientech, 2020)
Mimosa pudica L. is one of plants which is used as antidiarrhea by the common people in the society. The objectives of this research is to determine the compounds and antidiarrhea activity of ethanolic 96% Mimosa pudica L extract by using masers method. The method is divided 5 groups and its has 5 mices, which negatif group is given by NaCMC 0,5%, positive group given by Loperamide HCL with doses 0,0052 mg/20g, and the ethanol extract with doses (100, 200, dan 400 mg/kgBB). After 30 minutes treatment to animal study, it is continued by Oleum ricini p.o. Observation is done during 4 hours by observed some parameter such as frequency of diarrhea and weight of feses. The result of compound Mimosa pudica L. extract such as alkaloid, flavonoid, tanin, saponin, and steroid. The data is analyzed by using Man Whitney showed Mimosa pudica L extract doses 400 mg/kgBB is efectives doses such as antidiarrhea which is able to decrease the frequency of diarrhea (P>0,585) and weight of feses (P>0,754).